Involvement of Cytochrome P-450 in n-Butyl Nitrite-Induced Hepatocyte Cytotoxicity: n-Butyl nitrite cytotoxicity - Niknahad, Hossein; J. O’Brienb, Peter (Iranian Journal of Pharmaceutical Sciences, 2005)
Addition of n-butyl nitrite to isolated rat hepatocytes caused an immediate glutathione depletion followed by an inhibition of mitochondrial respiration, inhibition of glycolysis and ATP depletion. At cytotoxic butyl nitrite concentrations, lipid peroxidation occurred before the plasma membrane was disrupted. Cytochrome P-450 inhibitors inhibited peroxynitrite formation and prevented butyl nitrite-induced mitochondrial respiration inhibition, ATP depletion, lipid peroxidation and plasma membrane disruption. However, glutathione depletion, S-nitroso-glutathione (GSNO) formation, or the inhibition of glycolysis was not affected by cytochrome P-450 inhibitors. Glutathione-depleted hepatocytes were resistant to butyl nitrite which suggests that cytotoxicity and peroxynitrite formation results from GSNO formation. Peroxynitrite formation was also inhibited by reactive oxygen scavengers. These findings suggest that cytochrome P-450 isoforms (particularly CYP2E1) act as a source of superoxide anion radicals in the formation of cytotoxic peroxynitrite from nitric oxide.